Pendampingan Pembuatan Legal Drafting Akad Mudharabah di Desa Battal Panji Situbondo - Zaini Miftah; Mohammad Faizin; Aisyi Karim; Ahmad Mujib Hasan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of writing this article is to provide protection of the law, as well as providing stronger legal certainty for people who make an agreement. This is because, with the existence of Legal Drafting or written agreement, there is authentic evidence that cannot be contested so that one of the parties in default can be subject to inviolable so that one of the parties in default can be subject to legal legal policy. Therefore, the existence of Legal Drafting is very important. its position, especially for the practice of Mudharabah contract agreements. then in our community service programme, we provide legal drafting efforts to the Battal village community. Legal Drafting to the Battal Situbondo village community with the aim of increasing the legal awareness of the Battal village community in making Legal Drafting, reviewing the lack of Battal village community towards the importance of Legal Drafting in the agreement. The implementation method used in this service This is a method of delivering Legal Drafting material; both in the form of understanding, the laws that regulate it, the benefits and objectives of Legal Drafting, then followed by a discussion session. Drafting, then continued with a discussion session and finally helped the community make Legal Drafting. the community to make Legal Drafting. The success index of this service programme success index of this service programme is to reach 61% of 27% in the community's understanding of legal drafting. Legal Drafting, while the Battal village community's obedience index has increased from 36% to 57%. increased from 36% to 57%.